2005
DOI: 10.1088/0953-8984/17/22/024
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance characterization of defects produced by ion implantation into silicon

Abstract: Many of the defects created by ion implantation into silicon can be detected by electron paramagnetic resonance (EPR). The main defects observed are isolated point defects such as Si-P3 centres (neutral 4-vacancies),silicon dangling bonds in amorphous silicon and defects associated with the so-called resonance-a single broad anisotropic line; particular attention is paid to the latter defects as they have the highest population over a wide fluence range. This paper reports the effects on the nature and populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The saturation behavior is also reflected in optical characterizations. Considering these results and putting them in perspective with other experimental results 17,19,20,37,38 and simulations 12,14,15 obtained for c-Si leads us to conclude that the annealing of implanted ͑and dynamically annealed͒ crystalline silicon is dominated, at least in its initial stages, by the relaxation and the annealing of damage zones that are structurally very similar if not identical to a-Si. This also applies to the primary knock-ons of a few kiloelectron volts generated by light, high-energy ions.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The saturation behavior is also reflected in optical characterizations. Considering these results and putting them in perspective with other experimental results 17,19,20,37,38 and simulations 12,14,15 obtained for c-Si leads us to conclude that the annealing of implanted ͑and dynamically annealed͒ crystalline silicon is dominated, at least in its initial stages, by the relaxation and the annealing of damage zones that are structurally very similar if not identical to a-Si. This also applies to the primary knock-ons of a few kiloelectron volts generated by light, high-energy ions.…”
Section: Discussionsupporting
confidence: 53%
“…From the experimental point of view, Barklie and O'Raifeartaigh 37 recently performed electron paramagnetic resonance ͑EPR͒ measurements on ion-implanted Si and suggested that a broad line in the signal, overlooked in previous investigations, is related to these amorphous pockets. They show that these defects are already present after low-fluence implantation and in much larger concentration than other, simpler PD, at least for heavy ion or lower energy ion implantation.…”
Section: B General Discussionmentioning
confidence: 99%
“…The study of defects formed in silicon by ion implantation has been a major research issue for many years [1][2][3]. Since silicon remains the key material of semiconductor device manufacturing, this area of study continues to be important, especially in relation to integration of electronics and spintronics on a single wafer.…”
Section: Introductionmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) is the characterization method for the identification of the dopants and defects created during the implantation process and the investigation of their microscopic structure 1,2 . However, conventional EPR measurements can usually only be performed on samples implanted with relatively high ion energies and ion doses to get the necessary number of defects.…”
mentioning
confidence: 99%
“…In the fabrication of semiconductor devices, ion implantation is widely used to create thin layers doped with different impurities for the realization of, e.g., pn junctions or ohmic contacts. Electron paramagnetic resonance (EPR) is the characterization method for the identification of the dopants and defects created during the implantation process and the investigation of their microscopic structure 1,2 . However, conventional EPR measurements can usually only be performed on samples implanted with relatively high ion energies and ion doses to get the necessary number of defects.…”
mentioning
confidence: 99%